DESMOID-TYPE FIBROMATOSIS IN THE MALE BREAST MIMICKING CANCER - Ramos, Lilian de Sá Paz; Biazús, Jorge Villanova; Damin, Andréa Pires Souto; Rocha, Sálvia Maria Canguçu da; Silva, Ana Claudia Imbassahy de Sá Bittencourt Câmara e (Mastology, 2020)
Introduction: Desmoid-type fibromatosis (DTF) is defined as a clonal proliferation of fibroblasts that emerges in soft tissues, with a tendency to infiltrate local tissues and toward local recurrence, but with no potential of distant metastases. The breast is an unusual location, corresponding to approximately 0.2% of all breast tumors. The literature has few DTF cases described in the male breast. The etiology of the lesion is unclear. Fibromatosis presents as a firm, painless, and mobile mass, which can be fixed to the pectoralis major or the skin. Radiological characteristics are nonspecific. The lesion manifests as a suspicious solid mass with irregular margins, making it difficult to differentiate the lesion from breast cancer on mammography, ultrasound, and magnetic resonance imaging. Immunohistochemistry (IHC) shows positivity for vimentin, ß-catenin, and actin, with negative desmin. Standard treatment consists of resection of the lesion with margins. Objective: To report a rare case of DTF in the male breast. Method: This is the description of the clinical case based on medical records. Result: A 42-year-old man had a nodule in the left breast for 1 year. He had no medical or family history of breast cancer. The patient presented a firm tumor with ill-defined margins, slightly mobile, adhered to the skin, measuring 5 cm, in the left upper inner quadrant during physical examination. Mammography showed asymmetry in the left breast, BI-RADS 4 Core biopsy indicated fibrosis, with segmental resection of the lesion. Histology revealed fibrous infiltrative neoplasm, with an intense collagenic aspect, 3.5 cm, and free margins. IHC was positive for vimentin, actin, and β-catenin, compatible with DTF. Conclusion: DTF in the male breast is a rare, locally invasive, benign tumor. It presents suspicious clinical and radiological aspects similar to those of breast cancer. The main treatment consists of resection of the lesion with satisfactory margins.